2019
DOI: 10.1101/833103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive whisker kinematics reveal context-dependent sensorimotor strategies

Abstract: 10Animals actively move their sensory organs in order to acquire sensory information. Some rodents, such 11 as mice and rats, employ cyclic scanning motions of their facial whiskers to explore their proximal 12surrounding, a behavior known as whisking. Here we investigated the contingency of whisking kinematics 13 on the animal's behavioral context that arises from both internal processes (attention and expectations) 14and external constraints (available sensory and motor degrees of freedom). We recorded rat w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Whisker bending, a commonly used proxy for contact force (Birdwell et al, 2007; but see also Quist et al, 2014;Yang and Hartmann, 2016), was dynamic (Figure 2F); a whisker could bend slightly while pushing into a shape and then bend in the other direction while detaching. Occasionally, we observed double pumps, a signature of active exploration (Wallach et al, 2020). The contact forces we observed were much smaller than in many studies; the typical maximum bend (Dk) was 5.1 ± 1.0 m À1 for C1, 11.2 ± 1.2 m À1 for C2, and 19.1 ± 3.3 m À1 for C3 (mean ± SEM over mice; Figures 2G and S2F), much less bent than the 50-150 m À1 typical of pole localization (Hires et al, 2015;Hong et al, 2018;Huber et al, 2012).…”
Section: Contact Count But Not Whisking or Contact Force Differs Betw...mentioning
confidence: 86%
“…Whisker bending, a commonly used proxy for contact force (Birdwell et al, 2007; but see also Quist et al, 2014;Yang and Hartmann, 2016), was dynamic (Figure 2F); a whisker could bend slightly while pushing into a shape and then bend in the other direction while detaching. Occasionally, we observed double pumps, a signature of active exploration (Wallach et al, 2020). The contact forces we observed were much smaller than in many studies; the typical maximum bend (Dk) was 5.1 ± 1.0 m À1 for C1, 11.2 ± 1.2 m À1 for C2, and 19.1 ± 3.3 m À1 for C3 (mean ± SEM over mice; Figures 2G and S2F), much less bent than the 50-150 m À1 typical of pole localization (Hires et al, 2015;Hong et al, 2018;Huber et al, 2012).…”
Section: Contact Count But Not Whisking or Contact Force Differs Betw...mentioning
confidence: 86%
“…6A), encoding of self-motion in the paralemniscal thalamus was relatively poor in awake, head-fixed rats (Moore et al, 2015;Urbain et al, 2015). Future studies could explore the possibility that, as shown for other modalities (Roberts and Bell, 2000), descending input or feedback either gates or cancels this activity, perhaps in a context-dependent manner (Wallach et al, 2020).…”
Section: Comparison With Results From Awake Behaving Ratsmentioning
confidence: 83%
“…76 Rodents sweep their whiskers in concert with other autonomic or voluntary rhythmic behaviors, such as respiration, locomotion, sniffing, and grooming. 9,47,[77][78][79] The two sets of whiskers can move synchronously or asynchronously depending on the behavioral context. For instance, asymmetric whisker movements can predict a turning of the head.…”
Section: Ethology Of Symmetric and Asymmetric Whisker Movementsmentioning
confidence: 99%